Perbedaan Paradigma Kosmologi Antara Stephen Hawking dan Al-farabi - Fitri Lindayunita (Astroislamica: Journal of Islamic Astronomy, 2025)
Cosmology, as a branch of science that studies the origin and structure of the universe has been a topic of debate throughout history. This article analyzes the differences in cosmological paradigms between Stephen Hawking a modern scientist who uses a theoretical physics approach, and Al-farabi a 9th century muslim philosopher who uses a metaphysical and theological approach in his understanding of cosmology. Hawking explains cosmological phenomena through several concepts such as singularity, multiverse, and black hole without involving theological aspects, while Al-farabi uses the concept of emanation where there is God’s involvement as the creator. This research uses a literature study to compare the two approaches and their impact on people’s understanding of the universe. The analysis shows that their thoughts open up opportunities for dialogue between modern science and religion, and provide a more logical perspective in understanding the relationship between science and spirituality.